DNA barcoding for identification of some fish species (Carangidae) in Vietnam coastal area - Thu, Pham The; Linh, Nguyen Manh; Quan, Nguyen Van; Chien, Pham Van; Ly, Dao Huong; Hiep, Le Ba Hoang (Vietnam Journal of Marine Science and Technology, 2020)
Carangidae family has got about 148 species belonging to 32 genera. In Vietnam, Carangidae is of high commercial value and playing an important role in the ecosystem. In the context Vietnam has received yellow card for seafood since Nov. 2017 by the EU, in which one of the main reasons was related to the restriction of traceability. In this study, DNA barcoding technique of mitochondrial cytochrome oxidase I (COI) gene was used to classify 56 specimens of Carangidae from three coastal areas (Northern, Central and Southern) in Vietnam to evaluate the effectiveness compared to the morphological classification method. Results showed that 21 species belonging to 16 genera were determined by the COI barcode while 18 species (16 genera) were determined when using morphological method. Seriola quinqueradiata and Trachinotus anak were newly recorded in Vietnam. From 56 sequences with 660 bp of mtDNA (COI), total 27 haplotypes were detected; haplotype diversity (h) and nucleotide diversity (π) were 0.903 ± 0.00060 and 0.14%, respectively. The DNA barcodes of COI gene of 21 species in Carangidae which were developed in this study could be used as a basis for comparison and traceability of their products. In addition, the results showed the high potentiality in using COI barcode to identify Carangidae fish in Vietnam.